A Survey Addressing On-Chip Interconnect: Energy and Reliability Considerations. (26th March 2012) - Postman, Jacob; Chiang, Patrick
Abstract : Scaling CMOS process technology continues to enable increased levels of system integration, leading to on-chip communication demands beyond what traditional digital signaling techniques can efficiently provide with sufficient reliability. In this paper we survey the state of the art of on-chip interconnect techniques for improving performance, energy, and reliability and provide a review of interconnect reliability considerations. Finally, we provide a case study to evaluate the efficiency of error correcting codes on a state-of-the-art energy-efficient low-swing interconnect.